Laminated aluminum sheet convenient for laser marking and preparation method thereof
The introduction of a water-soluble composite resin coating on laser-markable overlay aluminum sheets addresses issues of membrane bubbling and low accuracy in existing technologies, achieving efficient, precise, and clear laser coding by utilizing a specific formulation of water, high-molecular-weight resin, self-luminescent materials, and inorganic fillers.
Patent Information
- Application Number
- CN202411938471.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
Current overlay aluminum sheets for printed circuit boards face issues such as membrane bubbling, unclear markings, slow marking speed, and low accuracy during laser coding, which hinder production efficiency in the manufacturing process.
A laser-markable overlay aluminum sheet is developed, featuring a water-soluble composite resin coating comprising water, high-molecular-weight resin, thermally stable materials, self-luminescent materials, metal powders, oxide and silicate inorganic fillers, and functional additives, which reduces the energy required for laser coding, increases speed and accuracy, and enhances marking clarity.
The optimized coating formulation results in lower energy requirements, faster and more precise laser coding with clearer markings, and improved recognition of two-dimensional codes, even in low-light conditions, by leveraging the properties of high-molecular-weight resins, self-luminescent materials, and inorganic fillers.
Abstract
Description
Technical Field
[0001] The invention relates to a printed circuit board, and in particular to a coated aluminum sheet convenient for laser marking and a preparation method thereof. Background Art
[0002] In recent years, before mechanical drilling, printed circuit board factories will use fiber lasers to print QR codes on the surface of coated aluminum cover plates. The QR codes can be subsequently recognized by the machine, and the corresponding drilling production operations are performed according to the drilling program information corresponding to the QR code. The main principle of the laser coding process is to use a high-energy laser beam to irradiate the film layer on the surface of the aluminum sheet. The film material absorbs the laser energy and produces a thermal excitation process in the irradiated area, thereby causing the surface temperature of the material to rise and a series of physical or chemical changes to occur, such as melting, gasification, oxide formation, discoloration, etc., leaving a permanent mark on the film surface. However, most of the coated aluminum sheet products currently often have problems such as film blistering, unclear graphics, slow marking speed, and low precision during the laser coding process, which seriously affects the production efficiency of printed circuit board factories.
[0003] Therefore, it is necessary to develop a coated aluminum sheet that is convenient for laser marking and a preparation method thereof. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a film-coated aluminum sheet that is convenient for laser marking and a preparation method thereof, wherein the film-coated aluminum sheet that is convenient for laser marking comprises an aluminum foil and a water-soluble composite resin coating coated on the surface thereof; the raw materials for preparing the water-soluble composite resin coating comprise water, polymer resin, solid-solid phase change material, self-luminous material, metal powder, oxide and silicate inorganic filler, and functional additive. The present invention can make the energy required for laser coding lower, the speed faster, the accuracy higher, and the marking clearer by rationally matching the raw materials.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a film-coated aluminum sheet that is convenient for laser marking, wherein the film-coated aluminum sheet that is convenient for laser marking comprises an aluminum foil and a water-soluble composite resin coating coated on the surface thereof;
[0007] Among them, in parts by mass, the raw materials for preparing the water-soluble composite resin coating include:
[0008] 40-50 parts of water, for example 40 parts, 41 parts, 43 parts, 45 parts, 46 parts, 48 parts or 50 parts, etc.;
[0009] 40-60 parts of polymer resin, for example, 40 parts, 43 parts, 45 parts, 48 parts, 50 parts, 52 parts, 55 parts, 58 parts or 60 parts, etc.;
[0010] 15-35 parts of solid-solid phase change material, for example, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 27 parts, 30 parts, 33 parts or 35 parts, etc.;
[0011] 0.5-1 part of self-luminous material, for example, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part, etc.;
[0012] 0.1-0.6 parts of metal powder, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts, etc.;
[0013] The oxide and silicate inorganic fillers are 8-30 parts, for example, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts or 30 parts.
[0014] The functional additive is 0.2-4 parts, for example, 0.2 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts.
[0015] The water-soluble composite resin coating of the present invention can make the energy required for laser coding lower, the speed faster, the precision higher, and the marking clearer by preparing the raw materials reasonably. The principles of laser marking include: 1. The polymer resin helps the film layer absorb laser energy, so that the components of the film layer undergo a chemical reaction of carbonization, thereby leaving a clear mark; 2. The self-luminous material makes the two-dimensional code of the film layer easier to identify under darker light; 3. The oxide and silicate inorganic fillers can adjust the color and brightness of the film layer to make the contrast stronger; 4. The fine metal powder makes the light reflected by the film layer brighter and more uniform, and the smaller the particle size of the metal powder, the higher the reflectivity.
[0016] As a preferred technical solution of the present invention, the functional additives include, by weight, and by weight:
[0017] Dispersant 0.5-1 part, for example 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part, etc.;
[0018] 0.3-1 part of leveling agent, for example, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part, etc.;
[0019] 0.2-0.6 parts of defoaming agent, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts, etc.;
[0020] 0.2-0.6 parts of antioxidant, for example 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts, etc.;
[0021] 0.2-0.6 parts of preservatives, for example 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts, etc.
[0022] As a preferred technical solution of the present invention, the polymer resin includes any one of water-based acrylic emulsion, water-based polyurethane emulsion, and water-based polyamide emulsion, or a combination of at least two of them.
[0023] Preferably, the aqueous acrylic emulsion includes any one of aqueous styrene acrylic emulsion, aqueous silicone acrylic emulsion, aqueous pure acrylic emulsion or acetic acid acrylic emulsion, or a combination of at least two thereof.
[0024] It should be noted that the polymer resin can improve the adhesion of the film layer to the aluminum foil, and at the same time has a strong absorption effect on laser energy, causing a carbonization reaction to form a clear mark on the surface of the film layer that is different from its original color.
[0025] As a preferred technical solution of the present invention, the solid-solid phase change material includes a polyethylene glycol-modified solid-solid phase change material and / or a composite polyol-based solid-solid phase change material.
[0026] Preferably, the polyethylene glycol-modified solid-solid phase change material includes: polyethylene glycol-cellulose diacetate graft copolymer, polyethylene glycol-hydroxypropyl methylcellulose graft copolymer, polyethylene glycol-polyvinyl alcohol graft copolymer, polyethylene glycol-acrylonitrile-itaconic acid graft copolymer, polyethylene glycol-polybutylene succinate graft copolymer, polyethylene glycol-diphenylmethane diisocyanate-polyvinyl alcohol cross-linked copolymer, polyethylene glycol-sorbitol-dipentaerythritol-inositol cross-linked copolymer, polyethylene glycol-cyclodextrin-diphenylmethane diisocyanate, or a combination of at least two thereof.
[0027] It should be noted that the most commonly used heat dissipation material at present is solid pure PEG, whose phase change behavior belongs to solid-liquid phase change. During the phase change process, a liquid with a certain fluidity is generated, and the thermal conductivity is low, and there may be a risk of adhesion of drill cuttings and aluminum wires; while the polyethylene glycol-modified solid-solid phase change material is the product of polyethylene glycol (PEG) modification, and they are all polymer solid-solid phase change materials with moderate phase change temperature, large phase change enthalpy, and no liquid is generated during the phase change process. While efficiently dissipating heat, it also reduces the risk of wire entanglement and hole plugging.
[0028] Preferably, the composite polyol-based solid-solid phase change material comprises any one or a combination of at least two of pentaerythritol-trimethylolethane (PE-PG), pentaerythritol-neopentyl glycol (PE-NPG), neopentyl glycol-trimethylolaminomethane (NPG-TAM), (2-amino-2-methyl-1,3-propanediol)-trimethylolaminomethane (AMPD-TAM), pentaerythritol-trimethylolaminomethane (PE-TAM), trimethylolethane-(2-amino-2-methyl-1,3-propanediol) (PG-AMPD), and neopentyl glycol-trimethylolaminomethane-pentaerythritol (NPG-TAM-PE).
[0029] It should be noted that the solid-solid phase transition temperature of monovalent polyol materials is relatively high. Compounding them into multivalent polyol materials can further improve the thermal properties of the materials, broaden the phase change temperature zone, and be more suitable for the temperature change requirements during the drilling process.
[0030] As a preferred technical solution of the present invention, the self-luminous material includes any one of gallium oxide, strontium oxide, zinc sulfide, strontium sulfide, barium sulfide, and calcium sulfide, or a combination of at least two thereof. In addition to the above-mentioned sulfide series self-luminous materials, self-luminous materials such as aluminate system and silicate system can be considered.
[0031] As a preferred technical solution of the present invention, the metal powder includes aluminum powder, which can make the light reflected by the film layer brighter and more uniform.
[0032] Preferably, the oxide and silicate inorganic fillers include any one or a combination of at least two of titanium dioxide, silicon dioxide, magnesium oxide, aluminum oxide, zinc oxide, chromium trioxide, neodymium oxide, bismuth oxide, tin oxide, talc, calcium carbonate, aluminum hydroxide, magnesium hydroxide, and kaolin. In addition to oxides and silicates, other color powders can also be selected as inorganic fillers, which can also adjust the color and brightness of the film layer to make the laser coding contrast stronger.
[0033] As a preferred technical solution of the present invention, the thickness of the aluminum foil is 70-150μm, for example, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm or 150μm, and the thickness of the water-soluble composite resin coating is 20-100μm, for example, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or 100μm, etc.
[0034] In a second aspect, the present invention provides a method for preparing the coated aluminum sheet that is convenient for laser marking according to the first aspect, the preparation method comprising the following steps:
[0035] (1) mixing water, a self-luminous material, a metal powder, an oxide and a silicate inorganic filler uniformly according to parts by mass, and sand-milling the mixture to obtain a first dispersion;
[0036] (2) mixing the polymer resin and the solid-solid phase change material uniformly according to parts by mass to obtain a second dispersion;
[0037] (3) adding the first dispersion into the second dispersion, and then adding a functional additive, and sequentially stirring, homogenizing, dispersing, filtering, and vacuuming to defoam to obtain a water-soluble composite glue;
[0038] (4) coating the water-soluble composite glue on the surface of the aluminum foil and drying it to obtain a coated aluminum sheet that is convenient for laser marking;
[0039] There is no order of precedence between step (1) and step (2).
[0040] As a preferred technical solution of the present invention, the functional auxiliary agent includes a dispersant, and the dispersant is added in step (1) to prepare the first dispersion.
[0041] As a preferred technical solution of the present invention, the maximum particle size in the first dispersion is less than 20 μm.
[0042] And / or, in step (1), water and dispersant are first mixed evenly, and then the remaining raw materials are added and mixed evenly. It should be noted that the remaining raw materials include self-luminous materials, metal powders, oxides and silicate inorganic fillers.
[0043] And / or, the drying temperature in step (4) is 110-130°C, for example, 110°C, 115°C, 120°C, 125°C or 130°C, and the drying time is 5-10min, for example, 5min, 6min, 7min, 8min, 9min or 10min, etc.
[0044] It should be noted that the filtration in step (3) is used to filter out undissolved large particles, for example, using a 280-mesh filter cloth.
[0045] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0046] The water-soluble composite resin coating of the present invention can make the energy required for laser coding lower, the speed faster, the precision higher, and the marking clearer by preparing the raw materials reasonably. The principles of laser marking include: 1. The polymer resin helps the film layer absorb laser energy, so that the components of the film layer undergo a chemical reaction of carbonization, thereby leaving a clear mark; 2. The self-luminous material makes the two-dimensional code of the film layer easier to identify under darker light; 3. The oxide and silicate inorganic fillers can adjust the color and brightness of the film layer to make the contrast stronger; 4. The fine metal powder makes the light reflected by the film layer brighter and more uniform, and the smaller the particle size of the metal powder, the higher the reflectivity. DETAILED DESCRIPTION
[0047] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Example 1
[0049] This embodiment provides a method for preparing a coated aluminum sheet that is convenient for laser marking, and the preparation method comprises the following steps:
[0050] (1) Add 40 parts of water to a reaction container, add 0.7 parts of dispersant (Japan Nopco dispersant SN5040) under high-speed stirring and stir for 0.5 hours, then slowly add 0.2 parts of fine aluminum powder, 2 parts of titanium dioxide, 1 part of silicon dioxide, 1 part of magnesium oxide, 0.5 parts of chromium trioxide, 0.2 parts of neodymium oxide, 6 parts of talc, 5 parts of calcium carbonate, 1 part of aluminum hydroxide, 0.1 parts of gallium oxide, 0.2 parts of zinc sulfide, and 0.2 parts of calcium sulfide, and stir and disperse at high speed for 2 hours; the above liquid is passed through a sand mill until the maximum particle size tested is less than 20 μm, to obtain a first dispersion;
[0051] (2) Take another reaction container, add 30 parts of water-based styrene-acrylic emulsion (Wanhua Chemical water-based styrene-acrylic emulsion), 5 parts of water-based silicone-acrylic emulsion (Rizhao Guangda Building Materials Co., Ltd. water-based silicone-acrylic emulsion), 7 parts of water-based polyurethane emulsion (Wanhua Chemical water-based polyurethane emulsion), 3 parts of water-based polyamide emulsion (Wanhua Chemical water-based polyamide emulsion), and stir at high speed for 0.5 h to mix evenly; then add 2 parts of polyethylene glycol-cellulose diacetate graft copolymer, 3 parts of polyethylene glycol-hydroxypropyl methylcellulose graft copolymer, 8 parts of polyethylene glycol-polyvinyl alcohol graft copolymer, 2 parts of polyethylene glycol-acrylonitrile-itaconic acid graft copolymer, 2 parts of polyethylene glycol-polybutylene succinate graft copolymer, 3 parts of pentaerythritol-trimethylolethane (PE-PG), 2 parts of pentaerythritol-neopentyl glycol (PE-NPG), 2 parts of neopentyl glycol-trimethylolaminomethane (NPG-TAM), stir at high speed for 2 h until all the solids are dissolved, to obtain a second dispersion;
[0052] (3) Slowly add the first dispersion into the second dispersion, then add 0.5 parts of leveling agent (Clariant 3060), 0.5 parts of defoaming agent (BASF 2410), 0.3 parts of antioxidant (BASF 1010), and 0.3 parts of preservative (Clariant CI15HS), stir at high speed for 1 hour, pass through a homogenizer and a disperser once each, continue stirring for 1 hour, filter, vacuum and defoam, and then obtain a water-soluble composite glue;
[0053] (4) coating the water-soluble composite glue on the surface of an aluminum foil with a thickness of 0.12 mm, controlling the coating thickness to be 60 μm after drying, and drying at 120° C. for 10 min to obtain a coated aluminum sheet that is convenient for laser marking;
[0054] There is no order of precedence between step (1) and step (2).
[0055] Example 2
[0056] This embodiment provides a method for preparing a coated aluminum sheet that is convenient for laser marking, and the preparation method comprises the following steps:
[0057] (1) Add 40 parts of water to a reaction container, add 1 part of dispersant (Japan Nopco dispersant SN5040) under high-speed stirring and stir for 0.5 hours; then slowly add 0.2 parts of fine aluminum powder, 3 parts of titanium dioxide, 1 part of silicon dioxide, 1 part of aluminum oxide, 1 part of zinc oxide, 0.2 parts of bismuth oxide, 0.1 parts of tin oxide, 5 parts of talc, 2 parts of magnesium hydroxide, 3 parts of kaolin, 0.2 parts of strontium oxide, 0.3 parts of barium sulfide, and 0.1 parts of calcium sulfide, and stir and disperse at high speed for 2 hours; the above liquid is passed through a sand mill until the maximum particle size tested is less than 20 μm, to obtain a first dispersion;
[0058] (2) Take another reaction container, add 25 parts of water-based pure acrylic emulsion (water-based pure acrylic emulsion of Rizhao Guangda Building Materials Co., Ltd.), 17 parts of acetyl acrylic emulsion (water-based acetyl acrylic emulsion of Dow), 10 parts of water-based polyurethane emulsion (water-based polyurethane emulsion of Wanhua Chemical), 2 parts of water-based polyamide emulsion (water-based polyamide emulsion of Wanhua Chemical), and stir at high speed for 0.5 hours to mix evenly; then add 10 parts of polyethylene glycol-polyvinyl alcohol graft copolymer, 2 parts of polyethylene glycol-acrylonitrile-itaconic acid graft copolymer copolymer, 3 parts of polyethylene glycol-polybutylene succinate graft copolymer, 4 parts of polyethylene glycol-diphenylmethane diisocyanate-polyvinyl alcohol cross-linked copolymer, 2 parts of pentaerythritol-neopentyl glycol (PE-NPG), 3 parts of (2-amino-2-methyl-1,3-propanediol)-trishydroxymethylaminomethane (AMPD-TAM), 2 parts of pentaerythritol-trishydroxymethylaminomethane (PE-TAM), stirring at high speed for 2 hours until all the solids are dissolved to obtain a second dispersion;
[0059] (3) Slowly add the first dispersion into the second dispersion, then add 0.6 parts of leveling agent (Clariant 3060), 0.5 parts of defoaming agent (BASF 2410), 0.3 parts of antioxidant (BASF 1010), and 0.3 parts of preservative (Clariant CI15HS), stir at high speed for 1 hour, pass through a homogenizer and a disperser once each, continue stirring for 1 hour, filter, vacuumize and defoam for standby use, and obtain a water-soluble composite glue;
[0060] (4) coating the water-soluble composite glue on the surface of an aluminum foil with a thickness of 0.12 mm, controlling the coating thickness to be 60 μm after drying, and drying at 120° C. for 10 min to obtain a coated aluminum sheet that is convenient for laser marking;
[0061] There is no order of precedence between step (1) and step (2).
[0062] Example 3
[0063] This embodiment provides a method for preparing a coated aluminum sheet that is convenient for laser marking, and the preparation method comprises the following steps:
[0064] (1) Add 40 parts of water to a reaction container, add 1 part of dispersant (Japan Nopco dispersant SN5040) under high-speed stirring and stir for 0.5 hours; then slowly add 0.3 parts of fine aluminum powder, 2 parts of titanium dioxide, 6 parts of talc, 5 parts of calcium carbonate, 1 part of magnesium oxide, 2 parts of aluminum hydroxide, 0.2 parts of gallium oxide, 0.1 parts of strontium sulfide, 0.1 parts of barium sulfide, and 0.1 parts of calcium sulfide, and stir and disperse at high speed for 2 hours; the above liquid is passed through a sand mill until the maximum particle size tested is less than 20 μm, to obtain a first dispersion;
[0065] (2) Take another reaction container, add 25 parts of water-based styrene-acrylic emulsion (Wanhua Chemical water-based styrene-acrylic emulsion), 15 parts of water-based pure acrylic emulsion (Rizhao Guangda Building Materials Co., Ltd. water-based pure acrylic emulsion), 11 parts of water-based polyurethane emulsion (Wanhua Chemical water-based polyurethane emulsion), 3 parts of water-based polyamide emulsion (Wanhua Chemical water-based polyamide emulsion), and stir at high speed for 0.5 h to mix evenly; then add 7 parts of polyethylene glycol-polyvinyl alcohol graft copolymer, 5 parts of polyethylene glycol-sorbitol -dipentaerythritol-inositol crosslinked copolymer, 5 parts of polyethylene glycol-cyclodextrin-diphenylmethane diisocyanate, 3 parts of pentaerythritol-trishydroxymethylaminomethane (PE-TAM), 2 parts of trimethylolethane-(2-amino-2-methyl-1,3-propanediol) (PG-AMPD), 5 parts of neopentyl glycol-trishydroxymethylaminomethane-pentaerythritol (NPG-TAM-PE), stirring at high speed for 2 hours until all the solids are dissolved to obtain a second dispersion;
[0066] (3) Slowly add the first dispersion into the second dispersion, then add 0.6 parts of leveling agent (Clariant 3060), 0.5 parts of defoaming agent (BASF 2410), 0.3 parts of antioxidant (BASF 1010), and 0.3 parts of preservative (Clariant CI15HS), stir at high speed for 1 hour, pass through a homogenizer and a disperser once each, continue stirring for 1 hour, filter, vacuumize and defoam for standby use, and obtain a water-soluble composite glue;
[0067] (4) coating the water-soluble composite glue on the surface of an aluminum foil with a thickness of 0.12 mm, controlling the coating thickness to be 60 μm after drying, and drying at 120° C. for 10 min to obtain a coated aluminum sheet that is convenient for laser marking;
[0068] There is no order of precedence between step (1) and step (2).
[0069] Comparative Example 1
[0070] This comparative example provides a method for preparing a coated aluminum sheet. Compared with Example 1, the only difference is that 0.2 parts of fine aluminum powder is completely omitted.
[0071] Comparative Example 2
[0072] This comparative example provides a method for preparing a coated aluminum sheet. Compared with Example 1, the only difference is that oxides and silicate inorganic fillers are completely omitted, that is, 2 parts of titanium dioxide, 1 part of silicon dioxide, 1 part of magnesium oxide, 0.5 parts of chromium trioxide, 0.2 parts of neodymium oxide, 6 parts of talc, 5 parts of calcium carbonate, and 1 part of aluminum hydroxide are completely omitted.
[0073] Comparative Example 3
[0074] This comparative example provides a method for preparing a coated aluminum sheet. Compared with Example 1, the only difference is that 0.7 parts of the dispersant is completely omitted.
[0075] The preparation methods described in the above embodiment and comparative example were respectively used to prepare 10 coated aluminum sheets, and then laser coding and marking verification was performed. The laser coding conditions were set as follows: time 5s, power 48%, frequency 700. If the two-dimensional code is clear and can be quickly recognized by the machine, it is qualified. If it cannot be recognized, it is unqualified, and the qualified rate is then obtained. Specific test information is shown in Table 1.
[0076] Table 1
[0077] project The number of coated aluminum sheets with qualified QR codes Number of coated aluminum sheets with unqualified QR codes QR code pass rate Example 1 10 0 100% Example 2 10 0 100% Example 3 10 0 100% Comparative Example 1 8 2 80% Comparative Example 2 7 3 70% Comparative Example 3 4 6 40%
[0078] It can be seen from Table 1 that:
[0079] (1) The water-soluble composite resin coatings in Examples 1-3 of the present invention can achieve lower energy, faster speed, higher precision, clearer marking, and a 100% pass rate for two-dimensional codes by rationally matching the raw materials for preparation;
[0080] (2) Comparing Example 1 with Comparative Example 1, since the fine aluminum powder is completely omitted in Comparative Example 1, the light reflected by the film layer is darker and the light uniformity is lower, which ultimately affects the two-dimensional code recognition and the pass rate of the two-dimensional code is reduced to 80%;
[0081] (3) Comparing Example 1 with Comparative Example 2, since the oxide and silicate inorganic fillers are completely omitted in Comparative Example 2, the color and brightness of the film layer are affected, and the contrast between the carbonized two-dimensional code and the film layer is low, which ultimately affects the recognition of the two-dimensional code, and the pass rate of the two-dimensional code is reduced to 70%;
[0082] (4) Comparing Example 1 with Comparative Example 3, since the dispersant is completely omitted in Comparative Example 3, the self-luminous material, metal powder, and inorganic filler are agglomerated and unevenly dispersed, which ultimately affects the uniformity of the overall color and brightness of the film layer, seriously affecting the clarity of the two-dimensional code, causing the pass rate of the two-dimensional code to drop to 40%.
[0083] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A coated aluminum sheet convenient for laser marking, characterized in that: The film-coated aluminum sheet convenient for laser marking comprises an aluminum foil and a water-soluble composite resin coating coated on the surface thereof; Wherein, in parts by mass, the raw materials for preparing the water-soluble composite resin coating include: 40-50 parts water; 40-60 parts of polymer resin; 15-35 parts of solid-solid phase change material; 0.5-1 part of self-luminous material; Metal powder 0.1-0.6 parts; 8-30 parts of oxide and silicate inorganic fillers; Functional additives 0.2-4 parts.
2. The film-coated aluminum sheet convenient for laser marking according to claim 1, characterized in that: In parts by mass, the functional additives include: Dispersant 0.5-1 part; Leveling agent 0.3-1 part; Defoaming agent 0.2-0.6 parts; Antioxidant 0.2-0.6 parts; Preservative 0.2-0.6 parts.
3. The film-coated aluminum sheet convenient for laser marking according to claim 1 or 2, characterized in that: The polymer resin includes any one of water-based acrylic emulsion, water-based polyurethane emulsion, and water-based polyamide emulsion, or a combination of at least two of them; Preferably, the aqueous acrylic emulsion includes any one of aqueous styrene acrylic emulsion, aqueous silicone acrylic emulsion, aqueous pure acrylic emulsion or acetic acid acrylic emulsion, or a combination of at least two thereof.
4. The film-coated aluminum sheet convenient for laser marking according to claim 1 or 2, characterized in that: The solid-solid phase change material includes a polyethylene glycol-modified solid-solid phase change material and / or a composite polyol-based solid-solid phase change material; Preferably, the polyethylene glycol-modified solid-solid phase change material includes: polyethylene glycol-cellulose diacetate graft copolymer, polyethylene glycol-hydroxypropyl methylcellulose graft copolymer, polyethylene glycol-polyvinyl alcohol graft copolymer, polyethylene glycol-acrylonitrile-itaconic acid graft copolymer, polyethylene glycol-polybutylene succinate graft copolymer, polyethylene glycol-diphenylmethane diisocyanate-polyvinyl alcohol cross-linked copolymer, polyethylene glycol-sorbitol-dipentaerythritol-inositol cross-linked copolymer, polyethylene glycol-cyclodextrin-diphenylmethane diisocyanate, or any one or a combination of at least two thereof; Preferably, the composite polyol-based solid-solid phase change material comprises any one of pentaerythritol-trimethylolethane, pentaerythritol-neopentyl glycol, neopentyl glycol-trimethylolaminomethane, (2-amino-2-methyl-1,3-propanediol)-trimethylolaminomethane, pentaerythritol-trimethylolaminomethane, trimethylolethane-(2-amino-2-methyl-1,3-propanediol), and neopentyl glycol-trimethylolaminomethane-pentaerythritol, or a combination of at least two thereof.
5. The film-coated aluminum sheet convenient for laser marking according to claim 1 or 2, characterized in that: The self-luminous material includes any one of gallium oxide, strontium oxide, zinc sulfide, strontium sulfide, barium sulfide, and calcium sulfide, or a combination of at least two of them.
6. The film-coated aluminum sheet convenient for laser marking according to claim 1 or 2, characterized in that: The metal powder includes aluminum powder; Preferably, the oxide and silicate inorganic fillers include any one or a combination of at least two of titanium dioxide, silicon dioxide, magnesium oxide, aluminum oxide, zinc oxide, chromium oxide, neodymium oxide, bismuth oxide, tin oxide, talc, calcium carbonate, aluminum hydroxide, magnesium hydroxide, and kaolin.
7. The film-coated aluminum sheet convenient for laser marking according to claim 1 or 2, characterized in that: The thickness of the aluminum foil is 70-150 μm, and the thickness of the water-soluble composite resin coating is 20-100 μm.
8. A method for preparing a film-coated aluminum sheet that is convenient for laser marking according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing water, a self-luminous material, a metal powder, an oxide and a silicate inorganic filler uniformly according to parts by mass, and sand-milling the mixture to obtain a first dispersion; (2) mixing the polymer resin and the solid-solid phase change material uniformly according to parts by mass to obtain a second dispersion; (3) adding the first dispersion into the second dispersion, and then adding a functional additive, and sequentially stirring, homogenizing, dispersing, filtering, and vacuuming to defoam to obtain a water-soluble composite glue; (4) coating the water-soluble composite glue on the surface of the aluminum foil and drying it to obtain a coated aluminum sheet that is convenient for laser marking; There is no order of precedence between step (1) and step (2).
9. The method for preparing a coated aluminum sheet that is convenient for laser marking according to claim 8, characterized in that: The functional auxiliary agent includes a dispersant, which is added in step (1) to prepare the first dispersion.
10. The method for preparing a coated aluminum sheet that is convenient for laser marking according to claim 9, characterized in that: The maximum particle size in the first dispersion is less than 20 μm; And / or, in step (1), firstly mix water and dispersant evenly, then add remaining preparation raw materials and mix evenly; And / or, the drying temperature in step (4) is 110-130° C. and the drying time is 5-10 min.